Modifikasi Algoritma XTEA dengan Pembangkitan Kunci Menggunakan Metode Linear Congruential Untuk Pengamanan File Dokumen - Berliana Oktaviani Sinaga; Sinar Sinurat; Taronisokhi Zebua (Journal of Informatics Management and Information Technology, 2021)
Confidential document files must have security both when the file process is sent or stored in the stroge media. This is done so that the confidential document file is not known by someone who does not have authority over the file, or to avoid loss if the file falls into the wrong hands. In order to achieve this, a document file security technique is needed that can convert document file data into unrecognized data. One of the techniques that can be used is cryptography. Cryptography makes use of algorithms to encode document files with an encryption process, and restore document files with a decryption process. One of the algorithms that can be used is the XTEA algorithm. XTEA divides the document file string into 2 parts, namely AL 32 bit and BL 32 bit. The weakness of the XTEA algorithm when carrying out the encryption or decryption process with repeated key scheduling so that it is not effective in optimizing the security of encrypted document files, therefore in this study the Linear Congruential Generator (LCG) method is added to generate XTEA keys. LCG has values ??a, c, m and X0 which triggers to get the XTEA key. So that in the process of distributing encrypted document files, the key sent is the LCG trigger value in the form of a, c, m and X0, if the value is known by the attacker, the encrypted document file cannot be returned. So that the results of the XTEA encryption algorithm with key optimizer based on the LCG method produce a document file cipher that is more optimal in security